Identification of p53 and Its Isoforms in Human Breast Carcinoma Cells - Zorka Milićević; Vladan Bajić; Lada Živković; Jelena Kasapović; Uroš Andjelković; Biljana Spremo-Potparević (The Scientific World Journal)
In breast carcinoma, disruption of the p53 pathway is one of the most common genetic alterations. The observation that the p53 can express multiple protein isoforms adds a novel level of complexity to the outcome of p53 mutations. p53 expression was analysed by Western immunoblotting and immunohistochemistry using monoclonal antibodies DO-7, Pab240, and polyclonal antiserum CM-1. The more frequently p53-positive nuclear staining has been found in the invasive breast tumors. One of the most intriguing findings is that mutant p53 appears as discrete dot-shaped regions within the nucleus of breast cancer cells. In many malignant cells, the nucleolar sequestration of p53 is evident. These observations support the view that the nucleolus is involved directly in the mediation of p53 function or indirectly by the control of the localization of p53 interplayers. p53 expressed in the nuclear fraction of breast cancer cells revealed a wide spectrum of isoforms. p53 isoforms ΔNp53 (47 kDa) and Δ133p53β (35 kDa), known as dominant-negative repressors of p53 function, were detected as the most predominant variants in nuclei of invasive breast carcinoma cells. The isoforms expressed also varied between individual tumors, indicating potential roles of these p53 variants in human breast cancer.